Absence of July Phenomenon in Acute Ischemic Stroke Care Quality and Outcomes - Gonzalez‐Castellon, Marco (J Am Heart Assoc, 2018)
BACKGROUND: Lower care quality and an increase in adverse outcomes as a result of new medical trainees is a concept well rooted in popular belief, termed the “July phenomenon.” Whether this phenomenon occurs in acute ischemic stroke has not been well studied. METHODS AND RESULTS: We analyzed data from patients admitted with ischemic stroke in 1625 hospitals participating in the Get With The Guidelines–Stroke program for the 5‐year period between January 2009 and December 2013. We compared acute stroke treatment processes and in‐hospitals outcomes among the 4 quarters (first quarter: July–September, last quarter: April–June) of the academic year. Multivariable logistic regression models were used to evaluate the relationship between academic year transition and processes measures. A total of 967 891 patients were included in the study. There was a statistically significant, but modest (<4 minutes or 5 percentage points) difference in distribution of or quality and clinical metrics including door‐to‐computerized tomography time, door‐to‐needle time, the proportion of patients with symptomatic intracranial hemorrhage within 36 hours of admission, and the proportion of patients who received defect‐free care in stroke performance measures among academic year quarters (P<0.0001). In multivariable analyses, there was no evidence that quarter 1 of the academic year was associated with lower quality of care or worse in‐hospital outcomes in teaching and nonteaching hospitals. CONCLUSIONS: We found no evidence of the “July phenomenon” in patients with acute ischemic stroke among hospitals participating in the Get With The Guidelines–Stroke program.